南太平洋、极地海域海洋大气烃类化合物分析研究 - 郑金树; 陈立奇; 林惠玲; 章增浩 (1994)
1992—1993年间采集了南极近海不同海域的大气样品,采用gC—MS测定,调查了其中有机物的种类,石油烃化合物的总量,并作了初步分析研究。 From November of 1992 to January of 1993, there were eight suspended particle samples, which were in the atmosphere over West South PaciFic Ocean and Antarctic waters, were taken in a voyage of an inverstigation ship (JI DI), the ship voyaged on Antarctic Waters and round earth For scientiFic inverstigation.Those samples were analysed by G C and GC-MS For hydrocarbon compounds.The results showed that concentrations of hydrocarbons in open ocean atmosphere were eFFected by New Guinea and New Zealand islands and trade wind zone, and decleased in Antarctic waters area obviously.The compounds such as dibutyl-phthalate, chloro-hexadecane, alkyl-phenol and alkyl-benzene were detected too.